Video Art: Everyday Fear within the Three Southern Thai Provinces - Phuyuthanon, I-na; Kumjim, Prapon (Journal of Urban Culture Research, 2014)
The objective of this project was to create a form of video art and utilize it to instill a social awareness of living everyday in fear as experienced by women who lost their husbands through the insurgency in Thailand’s three southern provinces. The overall objective of this video was to portray the personal and social atmosphere in terms of way of life, culture, and identity. The video is ten minutes long and consists of three stories: First, the ambience of the rubber plantation illustrating the unique culture in this region; Second, the tea drinking tradition of Thai Muslim men; Third, women suffering the loss during the insurgencies. Together the three accounts depicts how the lives of these women became a life of enduring suffering and loss. It is online at: www.youtube.com/watch?v=U-5pqeQKpiI.